Representasi Budaya dan Makna Simbolik Motif Kapal Kandas Kudus: Pendekatan Semiotika Roland Barthes - Yuli Astuti; Aditya Dimas Wahyu Sasongko; Muhammad Naoval Haris; Rizki Lestari; Zahir Widadi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Traditional batik is one of Indonesia’s cultural heritages that carries not only aesthetic value but also rich symbolism and philosophy. This study focuses on the Kapal Kandas Kudus motif, a coastal batik design rooted in the story of Admiral Cheng Ho’s shipwreck on Mount Muria. The motif contains symbolic elements that reflect the worldview of Kudus society, such as hope, life’s trials, balance, protection, and gratitude for natural abundance. The research employed a qualitative method through observation, interviews, documentation, and literature review, conducted at the Muria Batik Gallery, Kudus, which serves as a center for the development of Kudus batik. Roland Barthes’ semiotic approach was applied to reveal the denotative, connotative, and mythical meanings of various decorative elements, including ships, fish, seaweed, and coral reefs. The findings indicate that the Kapal Kandas motif was historically used in traditional ceremonies such as circumcisions and communal celebrations but has now become more flexible, being worn on diverse occasions. This shift illustrates cultural adaptability while maintaining symbolic values inherited from ancestors. The study emphasizes the importance of understanding the symbolic meanings of batik motifs as a means of cultural preservation and as a reinforcement of national identity.